A STYLISTIC STUDY OF LANGUAGE DEVIATION IN THOMAS HARDYâS THE RUINED MAID - Widayanti, Sukasih Ratna (MAGISTRA, 2014)
This study is aimed to describe the language deviation in a poem entitled The Ruined Maid by Thomas Hardy. In writing a poem, every poet has a poetic license to gain the beautiful poem even it creates language deviation. The poetic license may be ignoring the ordinary rule in making a word, phrase, or even sentence. The author of this poem, Thomas Hardy, is a good poet in performing his ideas through his poem. He intended to make his poem, The Ruined Maid, become unique and eye-catching poem. In Thomas Hardyâs The Ruined Maid, it can be concluded that there are five language deviations which is occurred. They are lexical deviation, grammatical deviation, graphological deviation, semantic deviation, and historical deviation. The language deviations are used to make a beautiful poem. Keywords: stylistic, language deviation